Reporting of conflicts of interest from drug trials in Cochrane reviews: cross sectional study. (20th August 2012) - Roseman, Michelle; Turner, Erick H; Lexchin, Joel; Coyne, James C; Bero, Lisa A; Thombs, Brett D
Abstract : Objectives To investigate the degree to which Cochrane reviews of drug interventions published in 2010 reported conflicts of interest from included trials and, among reviews that reported this information, where it was located in the review documents. Design Cross sectional study. Data sources Cochrane Database of Systematic Reviews . Selection criteria Systematic reviews of drug interventions published in 2010 in the Cochrane Database of Systematic Reviews, with review content classified as up to date in 2008 or later and with results from one or more randomised controlled trials. Results Of 151 included Cochrane reviews, 46 (30%, 95% confidence interval 24% to 38%) reported information on the funding sources of included trials, including 30 (20%, 14% to 27%) that reported information on trial funding for all included trials and 16 (11%, 7% to 17%) that reported for some, but not all, trials. Only 16 of the 151 Cochrane reviews (11%, 7% to 17%) provided any information on trial author-industry financial ties or trial author-industry employment. Information on trial funding and trial author-industry ties was reported in one to seven locations within each review, with no consistent reporting location observed. Conclusions Most Cochrane reviews of drug trials published in 2010 did not provide information on trial funding sources or trial author-industry financial ties or employment. When this information was reported, location of reporting was inconsistent across reviews.